2007
DOI: 10.1007/s00192-007-0314-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urinary incontinence in Taiwanese women aged 60 or over

Abstract: To determine risk factors of urinary incontinence (UI) in Taiwanese women aged 60 or over, face-to-face interviews with 1,517 women, selected by a multistage random method, were completed. The prevalence of UI in this age group was 29.8%. Factors and their prevalence associated with UI were age [odds ratio (OR)=1.04 per year], diabetes mellitus (39.8%, p = 0.002), hypertension (39.5%, p = 0.001), abdominal gynecological surgery (41.4%, p = 0.001), hysterectomy (42.4%, p = 0.003), history of drug allergy (41.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
8
1
3
Order By: Relevance
“…The present study also indicated that the prevalence of urinary incontinence increases with parity (OR 2.20; 95% CI, 1.27-3.78), which is consistent with results from other studies [10,12,13,18]. However, a small number of reports suggest that there is no such relationship [15,19].…”
Section: I-qol and Subscalessupporting
confidence: 94%
See 1 more Smart Citation
“…The present study also indicated that the prevalence of urinary incontinence increases with parity (OR 2.20; 95% CI, 1.27-3.78), which is consistent with results from other studies [10,12,13,18]. However, a small number of reports suggest that there is no such relationship [15,19].…”
Section: I-qol and Subscalessupporting
confidence: 94%
“…In the present study, BMI was not a risk factor for urinary incontinence-as reported by others [21]. However, some studies have concluded that such a relationship exists [4,8,10,18,19].…”
Section: I-qol and Subscalescontrasting
confidence: 42%
“…Female gender, diabetes, genitourinary surgery, dementia, education level, number of deliveries and hypertension were found to be related to UI in other studies as well [20][21][22][23][24][25][26]. Although the relationship between UI and hypertension is not fully understood, urgency and polyuria caused by antihypertensive drugs may be the reason.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, aging is a sophisticated process that is associated with different kinds of systemic diseases; for example, diabetes mellitus, hypertension, carcinoma and so on. Age is also an important risk factor of both UI and some risk factors of UI, including diabetes mellitus and hypertension 5 . Even if neuropathy as a result of alcohol consumption might be a cause of the etiological association between alcohol and the onset of UI in Taiwanese women aged 20–59 years, the study into risk factors for UI in Taiwanese women aged 60 years or over did not find that drinking alcohol had a significant association with UI.…”
mentioning
confidence: 94%
“…UI is a complex and common condition that can be found in women of all ages. Although the etiology of UI is still controversial, many studies show that age is significantly related to the risk of UI 4–6 . Furthermore, aging is a sophisticated process that is associated with different kinds of systemic diseases; for example, diabetes mellitus, hypertension, carcinoma and so on.…”
mentioning
confidence: 99%